Venous drainage of the left liver: an evaluation of anatomical variants and their clinical relevance. Issue 12 (December 2020) - Cawich, S.O.; Johnson, P.; Gardner, M.T.; Pearce, N.W.; Sinanan, A.; Gosein, M.; Shah, S.
Abstract : AIM: To evaluate the variations in venous drainage from the left liver. MATERIALS AND METHODS: A retrospective evaluation was performed of all consecutive abdominal computed tomography (CT) examinations at a tertiary referral facility between 1 January and 30 June 2018. Osirix (Pixmeo SARL, Bernex, Switzerland) was used to examine the major hepatic veins and their tributaries in each scan. The classification of variants as proposed by Nakamura and Tsuzuki was used to describe the findings. The following information was collected: ramification pattern, number, length and diameter of middle (MHV) and left (LHV) hepatic vein tributaries. Two researchers collected data independently, and the average measurements were used as the final dimensions. RESULTS: Of 102 examinations evaluated, only 27 demonstrated the conventional venous drainage patterns. The LHV and MHV combined to form a common trunk that emptied into the inferior vena cava (IVC) in 75 (73.5%) cases. The common trunk had a mean length of 8.89 mm and mean diameter of 20.18 mm. Other patterns included Nakamura and Tsuzuki type I (27.5%), type II (29.4%) and type III variants (16.7%). In addition, 4.9% of patients had absent superior middle veins and 80% had supernumerary short hepatic veins (4%). CONCLUSION: Only 26.5% of patients in this population had conventional venous drainage from the left liver. Surgeons and radiologists in hepatobiliary practice should be aware of these variants in order to minimise morbidity when performing invasive procedures. Highlights: Nakamura & Tsuzuki classification was used to describe hepatic vein variations. Only 26.5% of persons have conventional venous drainage from the left liver. The left and middle hepatic veins formed a common trunk in 73.5% persons. Other common patterns were type I (27.5%) and Type II (29.4%). Type III variants were least common (16.7%).